2005
DOI: 10.1523/jneurosci.0824-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Neurotrophins Are Required for the Induction of GABAergic Long-Term Potentiation in the Neonatal Rat Hippocampus

Abstract: In the developing rat hippocampus, GABAergic synapses undergo a Ca 2ϩ -dependent long-term potentiation (LTP GABA-A ); this form of synaptic plasticity is induced in CA3 pyramidal neurons by delivering repetitive depolarizing pulses (DPs) to the recorded neuron, and it is expressed as a long-lasting increase in the frequency and amplitude of spontaneous GABA A receptor-mediated postsynaptic currents. In the present study, we examined the role of endogenous tropomyosin-related kinase receptor B (TrkB) receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
(47 reference statements)
3
69
0
Order By: Relevance
“…BDNF infusion appears to enhance synaptic transmission (BDNF-LTP; Messaoudi et al, 2002, see also Lu et al, 2008. Analysis of LTP in hippocampal slices further demonstrated that application of repetitive depolarizing pulses failed to induce LTP in TrkB-IgG-incubated slices, whereas TrkA and TrkC-IgG had no effect (Gubellini et al, 2005, also Korte et al, 1998. TrkB Ab application was also shown to impair LTP induced by theta-burst or paired stimulation, leaving basal synaptic transmission and shortterm plasticity intact (Kang et al, 1997).…”
Section: Role Of Bdnf In In Vitro Classical Conditioningmentioning
confidence: 89%
“…BDNF infusion appears to enhance synaptic transmission (BDNF-LTP; Messaoudi et al, 2002, see also Lu et al, 2008. Analysis of LTP in hippocampal slices further demonstrated that application of repetitive depolarizing pulses failed to induce LTP in TrkB-IgG-incubated slices, whereas TrkA and TrkC-IgG had no effect (Gubellini et al, 2005, also Korte et al, 1998. TrkB Ab application was also shown to impair LTP induced by theta-burst or paired stimulation, leaving basal synaptic transmission and shortterm plasticity intact (Kang et al, 1997).…”
Section: Role Of Bdnf In In Vitro Classical Conditioningmentioning
confidence: 89%
“…One attractive candidate is BDNF, which plays a crucial role in synaptic plasticity (Poo, 2001), in GABA A -mediated LTP (Gubellini et al, 2005), and is known to be a potent regulator of spontaneous correlated network activity at early developmental stages (Aguado et al, 2003;Carmona et al, 2006). Although several lines of evidence indicate that BDNF can be released in a calcium-dependent way by depolarization of the postsynaptic cell (Goodman et al, 1996;Lessmann et al, 2003;Magby et al, 2006;Kuczewski et al, 2008a,b), the present data do not allow identifying the presynaptic or postsynaptic site of BDNF release.…”
Section: Discussionmentioning
confidence: 99%
“…One attractive candidate is BDNF, which can be released in a calciumdependent way by depolarization of the postsynaptic cell (Goodman et al, 1996;Lessmann et al, 2003;Magby et al, 2006;Kuczewski et al, 2008b). Previous studies from the immature hippocampus have shown that BDNF is the retrograde messenger required for increasing the probability of GABA and glutamate release at GABAergic and glutamatergic synapses, respectively (Gubellini et al, 2005;Mohajerani et al, 2007). Therefore, we tested whether BDNF was able to mimic the effects of STD-LTP on MF-evoked GPSCs.…”
Section: Pairing-induced Synaptic Potentiation Requires the Activatiomentioning
confidence: 99%
“…In CA3 pyramidal neurons, evidence has been provided that, during a restricted period of postnatal development, long-term changes in GABAergic synaptic transmission can be induced by repetitive depolarizing pulses (25,33,34). Although in these studies the conditioning protocol used for LTP induction could have been of physiological relevance, in the present case, the persistent enhancement of glutamatergic transmission at CA3-CA1 synapses depended on a calcium rise through a voltagedependent calcium channel activated by the depolarizing action of GABA during GDPs.…”
Section: Discussionmentioning
confidence: 99%
“…4). To better assess the contribution of endogenous TrkB ligands to GDP-induced potentiation, we incubated the slices for at least 3 h with a soluble form of TrkB receptor (TrkB-IgG) engineered as an immunoadhesin to prevent TrkB activation (24,25). In slices preincubated with 1 g/ml TrkB-IgGs, the pairing procedure did not affect the frequency or amplitude of sEPSCs (mean frequency values were 0.08 Ϯ 0.03 Hz in control and 0.08 Ϯ 0.02 Hz after pairing; n ϭ 6; P Ͼ 0.5; mean amplitude values were 18.9 Ϯ 2.7 pA in control and 17.7 Ϯ 2.2 pA after pairing; P Ͼ 0.5) (Fig.…”
Section: Pairing-induced Synaptic Potentiation Requires the Activatiomentioning
confidence: 99%